THE IMPACT OF SPECIFIC EXERCISES ON VOLLEYBALL PLAYERS' ABILITY TO IMPROVE THEIR SPEED AND QUICKNESS - Naser, Aqeel Yousif (Universitas Negeri Jakarta, 2026)
Background. Due to the fact that these are the player's own position changes, its important to work on improving these skills whether it be starting them or making sure we achieve those top levels of performance achievable. This is what the game is based on, along with a lot of basic technical skills — the player must move purposefully and variationally in as little time and with as little effort as possible. It also allows the player to toggle back and forth between offensive and defensive tasks. Knowledge of his work is part of success and part greatness. Objectives. The objective of the study is to develop training programs that can enhance agility and skill performance of junior volleyball players and determine how exercises enables junior volleyball players to increase their agility and skill performance. Method. By the trial method, the researcher had established comparable groups that were appropriate for the situation's kind. The study group consisted of players from Babylon Sports Club participating in the Iraqi Junior Volleyball League Championship for the period of 2024–2025. The participants were divided into two groups: The experimental group used workout sessions to increase speed and skill for hitting the volleyball, while the control group did not perform anything. This experimental group consisted of six junior volleyball players in addition to the team trainer. Results. This indicates that agility training improved performance of the skills. The researcher believes that it was the players' adherence to a standardized science-based training program that improved their performance on skill. Performance level indicates that this results in physical improvements and leads to the progress of volleyball-specific physical abilities. Conclusion. The study concluded that the recommended exercises have an effect in exercise volleyball spiking skills and agility skills volleyball spiking.